2014
DOI: 10.1177/1479972314538980
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective study on the effects of pulmonary rehabilitation in patients with pulmonary hypertension

Abstract: A retrospective analysis of 23 patients was undertaken to evaluate the outcome of pulmonary rehabilitation (PR) in patients with pulmonary hypertension (PH) over a preceding 6-year time frame. Chart review and data analyses were undertaken evaluating pulmonary arterial hypertension pharmacotherapy versus the same therapy with the addition of PR. Analysis included 23 patients who had a mean pulmonary artery pressure of 36.6 while on therapy and who had initial six-minute walk tests (6MWTs) ranging between 54 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 34 publications
2
9
0
5
Order By: Relevance
“…This result was confirmed by a retrospective study, which also showed a significant improvement by exercise training, with a higher benefit for those patients who had lower 6MWD at baseline [30]. …”
Section: Clinical Effects Of Exercise Training On Phsupporting
confidence: 66%
“…This result was confirmed by a retrospective study, which also showed a significant improvement by exercise training, with a higher benefit for those patients who had lower 6MWD at baseline [30]. …”
Section: Clinical Effects Of Exercise Training On Phsupporting
confidence: 66%
“…16 Eighteen studies were included in this review. All Englishlanguage articles of adults with PH were retrieved and considered.…”
Section: Search Methodsmentioning
confidence: 99%
“…[3][4][5] Moreover, patients often experience a significant decrease in their physical capacity and quality of life (QoL). [10][11][12] Exercise capacity is often evaluated with 6-minute walk test (6MWT) which exercise testing represents daily life physical activity (DLPA). [10][11][12] Exercise capacity is often evaluated with 6-minute walk test (6MWT) which exercise testing represents daily life physical activity (DLPA).…”
Section: Introductionmentioning
confidence: 99%